1999
DOI: 10.1002/1099-081x(199911)20:8<389::aid-bdd201>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of indomethacin and methotrexate on suppression of growth in rats

Abstract: The purpose of this study was to investigate the medium-term effects of methotrexate (MTX) and indomethacin on the growth of young rats. Four equal groups of Sprague-Dawley male rats (four animals in each group; mean+/-S.D. body weight, 183+/-13 g, in their rapid growth phase) were subjected to the following drug treatment: one group was given MTX (0.2 mg kg(-1) body weight) subcutaneously on every fourth day, another received indomethacin (2.5 mg kg(-1) body weight) subcutaneously daily and the third group wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The liver weights were significantly lower (AA-MTX versus AA, + p < 0.05; Table 3 ) only in the group of rats treated with MTX. The reduced weight of the liver in MTX-treated rats was assumed to be the result of inhibition of the pathway of de novo DNA synthesis by MTX [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The liver weights were significantly lower (AA-MTX versus AA, + p < 0.05; Table 3 ) only in the group of rats treated with MTX. The reduced weight of the liver in MTX-treated rats was assumed to be the result of inhibition of the pathway of de novo DNA synthesis by MTX [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moëll and Garwicz have reported that high-dose MTX produces short-term suppression of linear growth in rabbits (5). We have recently reported that MTX produces suppression of soft-tissue growth in rats and mice, possibly through the inhibition of the pathway of de novo DNA synthesis (6,7).…”
mentioning
confidence: 99%